The relationship between work life balance and organizational commitments of employees in oil and gas companies in Somalia - Ibrahim Barkhadle, Amina (2020)
The main purpose of this research is to examine the relationships between work life balance and organizational commitments of employees in oil and gas companies Somalia. The survey questionnaire was designed to elicit responses from the participants. A total of 175 questionnaires were distributed to the employees of companies that have been operating in Somalia namely Somalia Fuel Company, Hass petroleum, soma oil and gas. There are 148 usable questionnaires were returned, yielding a response rate of 15%. The collected data were analyzed using the Statistical Package for Social Science (SPSS) version 26. The results indicated that work life balance was positively related to organizational commitment. The result of this study provides a valuable information for human resource policy makers in the oil and gas sector to better plan and decide how to improve employee performance. Additionally, this finding could help human resource policy makers focus on the factors that improve commitment and work life balance among the employees in oil and gas companies.